2019
DOI: 10.1021/acs.energyfuels.9b02932
|View full text |Cite
|
Sign up to set email alerts
|

Stone Dust Looping for Ventilation Air Methane Abatement: A 1 m3/s Pilot-Scale Study

Abstract: Ventilation air methane (VAM) emissions are a significant contributor to fugitive greenhouse gas emissions at underground coal mines. The stone dust looping (SDL) process is a novel technology developed at The University of Newcastle, Australia, for VAM abatement. The SDL process is a cyclic process in which calcium oxide (CaO) is first obtained from the calcination of limestone (CaCO 3 ). CaO is then used to simultaneously oxidize VAM (methane concentrations of 0.1− 1 vol % in air) and capture carbon dioxide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…The main features of the VAM emissions are their low methane concentration (0.1-1%) and high flow rates (up to 600 m 3 /s), a direct upgrading of these streams being strongly hindered [6]. The most feasible and environmentally friendly solution is to pre-concentrate methane in these streams.…”
Section: Introductionmentioning
confidence: 99%
“…The main features of the VAM emissions are their low methane concentration (0.1-1%) and high flow rates (up to 600 m 3 /s), a direct upgrading of these streams being strongly hindered [6]. The most feasible and environmentally friendly solution is to pre-concentrate methane in these streams.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the measured values were different between the examined objects, but also depended on the currently conducted mining works (see Table 1). As reported by other sources, the VAM flow rate can achieve even 600 m 3 /s [19,20] and daily dust loading can reach 232 kg [21]. It should be considered that all mentioned parameters generate huge technical problems in the implementation of any known and available technology or currently being developed technology to an industrial scale.…”
Section: Characteristics Of the Vammentioning
confidence: 96%
“…CaCO 3 is then heated to regenerate CaO by burning the drainage gas, forming the calcium looping process. 164 Recently, Tremain et al 165 performed the 1 m 3 /s pilot-scale SDL research for VAM abatement. Over 99.5% methane conversion was achieved under 600 °C, and it was found that inventory size and VAM residence time are the key factors influencing the methane conversion.…”
Section: Application Status Of Tfrrmentioning
confidence: 99%